Analysis Of Kids Garden Dapodic Application System - Annisaa Miftakhul Jannah; Muqorobin Muqorobin; Wahyu Wijaya Widiyanto (Institut Teknologi Bisnis AAS Indonesia, 2020)
The dapodic system application is a system application that makes it easy for school users or operators to input all types of data related to school, such as active teacher data, non-active teacher data, active student data, non-active student data, report cards, schedules, and school facilities and infrastructure. The purpose of this research is to analyze how kindergarten school management is implemented with the dapodic application. The first method used is the data collection method, data analysis method, and system application implementation. The end result of this research is a perfect and maximum dapodic application that makes it easier for users to do their work.